2003
DOI: 10.1016/s0304-3975(02)00438-3
|View full text |Cite
|
Sign up to set email alerts
|

Finding the most vital node of a shortest path

Abstract: In the past, the problem of finding a most vital node of a given shortest path has been studied because of its implications in network management, where it is important to know in advance which component failure will affect network efficiency the most. In this paper, we show that this problem can be solved in O(m + n log n) time and O(m) space, where m and n denote the number of edges and the number of nodes in G.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 13 publications
0
52
0
Order By: Relevance
“…We have shown that, surprisingly, such a data structure can be stored using nearly the same space required to store a single distance matrix, while still supporting queries in constant time. Our oracle can easily be constructed in O(mn 2 +n 3 log n) time, matching the preprocessing time of all pairs variants of similar problems such as most vital node detection [18] and Vickrey pricing [11] in networks; while these algorithms require Θ(n 3 ) space, our oracle requires only O(n 2 log n) space. Furthermore, we have shown that by using O(n 2.5 ) space we can improve construction time to O(mn 1.5 + n 2.5 log n).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that, surprisingly, such a data structure can be stored using nearly the same space required to store a single distance matrix, while still supporting queries in constant time. Our oracle can easily be constructed in O(mn 2 +n 3 log n) time, matching the preprocessing time of all pairs variants of similar problems such as most vital node detection [18] and Vickrey pricing [11] in networks; while these algorithms require Θ(n 3 ) space, our oracle requires only O(n 2 log n) space. Furthermore, we have shown that by using O(n 2.5 ) space we can improve construction time to O(mn 1.5 + n 2.5 log n).…”
Section: Discussionmentioning
confidence: 99%
“…Of a similar flavor is the most vital node (or arc) problem [1,2,4,18], which is the problem of identifying the vertex (or edge) on a given shortest path, whose removal results in the longest replacement path.…”
mentioning
confidence: 99%
“…In this respect, a first result was obtained in [16], where an O(m + n log n) time algorithm was presented for the problem of finding a most vital node of a shortest path (i.e., a node whose removal induces a longest replacement shortest path between s and t). As the authors pointed out, such an algorithm can be used to implement a truthful mechanism for solving the shortest path problem in a communication network in which nodes are owned by selfish agents.…”
Section: Previous Resultsmentioning
confidence: 99%
“…In [CG84,SBvL87], it is proved that for any sequence of edge deletions that do not disconnect the graph, the diameter D of any unweighted graph turns to be less than D( + 1). Our work is also related to the computation of the most vital node of a shortest path [NPW03], that is the node whose removal results in the largest increase of the distance for a given pair of source/target, and the Vickrey pricing of edges [HS01].…”
Section: Related Workmentioning
confidence: 99%